2016
DOI: 10.11138/ccmbm/2016.13.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Early onset acute tubular necrosis following single infusion of zoledronate

Abstract: SummaryZoledronate is a highly potent bisphosphonate widely used in the treatment of postmenopausal osteoporosis. We report the first occurrence of toxic acute tubular necrosis (ATN) following treatment with zoledronate in a patient with osteoporosis. A 63-year-old Caucasian female with rheumatoid arthritis on anti-immune agents received a single dose of zoledronic acid (reclast) for worsening osteoporosis. Twelve days later, she developed renal failure with a rise in serum creatinine from a baseline level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Aliskiren (ROR 6.39) also has several published case reports of AKI, and new labeling was added to its package insert by the FDA in 2012 advising against concomitant use with angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers in patients with diabetes or renal impairment . Other new potential nephrotoxins such as everolimus (ROR 3.61) and zoledronic acid (ROR 2.23) have also been linked to nephrotoxicity in previous studies and reports …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Aliskiren (ROR 6.39) also has several published case reports of AKI, and new labeling was added to its package insert by the FDA in 2012 advising against concomitant use with angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers in patients with diabetes or renal impairment . Other new potential nephrotoxins such as everolimus (ROR 3.61) and zoledronic acid (ROR 2.23) have also been linked to nephrotoxicity in previous studies and reports …”
Section: Discussionmentioning
confidence: 93%
“…30 Other new potential nephrotoxins such as everolimus (ROR 3.61) and zoledronic acid (ROR 2.23) have also been linked to nephrotoxicity in previous studies and reports. [31][32][33] Although metformin and digoxin were among the new potential nephrotoxins with the highest AKI RORs (10.65 for metformin; 5.77 for digoxin), the literature provides less evidence for a direct association between these drugs and AKI. 34 The association seen here could be due to other risk factors for AKI that commonly affect patients taking these medications, including diabetes, heart failure, or advanced age.…”
Section: Drug-associated Aki In Faers Welch Et Almentioning
confidence: 99%
“…This nephrotoxicity occurs at variable intervals compared with the start of treatment with bisphosphonates (1-120 days) [5]. It appears to be dose-and infusion duration-dependent (1.5) but may also occur early and even after a single infusion of the drug, and without any risk factors favoring it [13].…”
Section: Discussionmentioning
confidence: 99%
“…There has been only one similar report involving a postmenopausal woman developing ATN within 12 days of an initial zoledronate infusion. 13 This 63-year-old woman was also on immunosuppressive medications, including low-dose prednisone, methotrexate, and tofacitinib. These similarities may suggest a potential interaction of immunosuppressive medications and zoledronate in postmenopausal women having underlying rheumatological disorders.…”
Section: Acute Tubular Necrosis Caused By Zoledronic Acid Infusion In...mentioning
confidence: 99%
“…These similarities may suggest a potential interaction of immunosuppressive medications and zoledronate in postmenopausal women having underlying rheumatological disorders. 13 Studies on rat models have shown that combination of methotrexate and zoledronate increases BMD in patients with inflammatory arthritis. 14 Further studies are needed to determine such interactions.…”
Section: Acute Tubular Necrosis Caused By Zoledronic Acid Infusion In...mentioning
confidence: 99%